Several separation properties in Binary Cech Closure Spaces - Chacko, Tresa Mary (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In our paper, "Separation, Connectedness and Compactness in Binary Cech Closure Spaces" we introduced and studied certian separation axioms. In this paper we study some semi higher separation axioms, mild separation axioms and higher separation axioms in Binary Cech Closure Spaces.